REPRESENTAMENT, OBJECT, AND INTERPRETANT ON NOVEL HARRY POTTER AND THE CHAMBER OF SECRETS - Putra, Juliandri Santika (Universitas Islam Negeri Sunan Gunung Djati, 2022)
This study aimed to describe role of represantement, object and interpretant in the cover of the novel Harry Potter And The Chamber of Secrets. This was a descriptive qualitative study. Data in the study were collected from the novel. It interprets that the signs and illustrations show fantasy which does not exist in real life. Colors which were discovered show the reality in the fantasy novel and the typography. The method uses to collect data was documentation with the following steps: (1) reading the novel, (2) interpreting the signs and colors displayed in the cover of the novel. In analyzing the data, the writer uses Peirce's theory of representation, object and interpretant for the main theory. The results of this study indicate that the signs, illustrations, typography and colors of the cover of the Harry Potter novel by J.K Rowling show the relationship between signs represented in one object, which has a strong and complementary character. The study concluded that the representation (sign) on the cover of the novel, while the object is the use of the image mark, such as place, cover title, publisher, player, and then Interpretation is the meaning about the sign.Â Keywords: semiotic, symbol, typography, color